2018
DOI: 10.1063/1.5038262
|View full text |Cite
|
Sign up to set email alerts
|

A novel density functional theory for atoms, molecules, and solids

Abstract: A theorem is proved stating that in atoms, molecules, and solids, only the set of the spherical parts of the density around each nucleus determines uniquely the external potential. Therefore, the induced Kohn and Sham (KS) potential has spherical symmetry around each nucleus, and furthermore, it has the symmetry of the external potential. In this way, the inconsistencies of standard density functional theory (DFT) concerning the asymmetry of the KS potential are remedied. As a result of the above, the ground s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
0
26
0
3
Order By: Relevance
“…The AIM "atoms in molecule theory" was utilized routinely to assess H-bond formation [55]. QTAIM "Bader's quantum theory of atoms" was applied using AIMAll [56], to detect the contribution of the intramolecular-forces of the molecular conformation inside the studied systems.…”
Section: Qtaim Nci and Elf Approachesmentioning
confidence: 99%
“…The AIM "atoms in molecule theory" was utilized routinely to assess H-bond formation [55]. QTAIM "Bader's quantum theory of atoms" was applied using AIMAll [56], to detect the contribution of the intramolecular-forces of the molecular conformation inside the studied systems.…”
Section: Qtaim Nci and Elf Approachesmentioning
confidence: 99%
“…r) не обладает симметрией внешнего потенциала из-за асимметрии электронной плотности. Подробное обсуждение проблемы асимметрии в ТФП и ее последствий можно найти в работах [8][9][10][11][12]. B недавней работе A.K.…”
Section: Introductionunclassified
“…B недавней работе A.K. Theophilou [12] доказал теорему, которая утверждает, что в атомах, молекулах и твердых телах только набор сферических частей плотности вокруг каждого ядра однозначно определяет внешний потенциал. Другими словами (см.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Furthermore, it has been suggested that only cer-tain subspaces of ρ(r) are relevant in DFT. 11,12 On the reverse, different energy-based modifications of DFAs, such as corrections for self-interaction errors, have been shown to affect the density in a similar way in localized regions. 13,14 Considering this, there is a possibility -and hope -that energy-based parametrization strategies indirectly improve the density in specially meaningful regions of space.…”
mentioning
confidence: 99%